1990
DOI: 10.1143/jjap.29.l2460
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Gallium Fluoride(GaF3)/GaAs Interface with and without Sulfur Treatment

Abstract: The electrical properties of gallium fluoride (GaF3) films deposited on GaAs are investigated. It has been found that deposited GaF3 films are good insulators with a dielectric constant of 6.6 and a resistivity of 2×1013 Ω·cm. It has also been found that the interface properties are good enough to generate inversion carriers either when a GaF3 film is deposited onto a homoepitaxial GaAs layer without breaking the vacuum or when the film is deposited on a sulfur-treated surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Recently, it was shown that a 10 eV band gap insulator, GaF 3 , can be grown on GaAs via exposure to various fluorine-based compounds (30,34,35,38,107,108,120,(123)(124)(125)(126). Operational devices have been constructed from GaF 3 -GaAs structures (124,125,(127)(128)(129), which demonstrates that the interface state density can be reduced to a sufficiently low level that GaF 3 may be a suitable insulator for GaAs-based devices. Hence, because of its potential technological importance, the reaction of atomic F with GaAs has been studied recently.…”
Section: Fluorinementioning
confidence: 99%
“…Recently, it was shown that a 10 eV band gap insulator, GaF 3 , can be grown on GaAs via exposure to various fluorine-based compounds (30,34,35,38,107,108,120,(123)(124)(125)(126). Operational devices have been constructed from GaF 3 -GaAs structures (124,125,(127)(128)(129), which demonstrates that the interface state density can be reduced to a sufficiently low level that GaF 3 may be a suitable insulator for GaAs-based devices. Hence, because of its potential technological importance, the reaction of atomic F with GaAs has been studied recently.…”
Section: Fluorinementioning
confidence: 99%